The Adobe Photoshop lightroom CC : 2015 release : lightroom 6 - Bē; Schönberger, Kilian; Evans, John; Straub, Katrin (Classroom in a book., 2015)
Serious digital photographers, amateur or pro, who seek the fastest, easiest, most comprehensive way to learn Adobe Photoshop Lightroom CC / Lightroom 6 choose Adobe Photoshop Lightroom CC 2015 release / 6 Classroom in a Book from the Adobe Creative Team at Adobe Press. The 11 project-based lessons in this book show readers step-by-step the key techniques for working in Photoshop Lightroom CC / 6. And a stunning showcase of extraordinary images by working professional photographers provides the perfect inspiration for your next project. Photoshop Lightroom CC / 6 delivers a complete workflow solution for the digital photographer, from powerful one-click adjustments to a full range of cutting-edge advanced controls. Readers learn how to manage large volumes of digital photographs, work in a non-destructive environment to allow for fearless experimentation, and perform sophisticated image processing tasks to easily produce good-looking pictures and polished presentations for both web and print. This completely revised Photoshop Lightroom CC / 6 edition explains how to edit and organize your images on mobile devices. Learn how to tag faces in your photo library for easier organization, and use Photo Merge to combine different exposures of the same subject to produce an HDR image. You'll also learn how to create stylish book designs that can be uploaded directly from Photoshop Lightroom for printing through the on-demand book vendor Blurb, or exported to PDF and printed on your own computer.